Aortic Root Replacement with conservation of the Aortic Valve using the Technique of Aortic Root Reimplantation in Large Aneuryms And High Grade Aortic Regurgitation (Latakia University Journal -Medical Sciences Series, 2024)
Aortic root reimplantation is an ideal choice in the treatment of aortic root aneurysms with or without aortic regurgitation. However, some surgeons may consider large aneurysms as a contraindication to this procedure referring to the technical complexity and the possible need to additional interventions to repair the regurgitating valveIn this article we represent a clinical case of a patient with severe dilatation of the aortic root reaching 72 mm, and severe aortic regurgitation, where we performed a conservative procedure using the technique of reimplantation as described by Tirone David; with an excellent outcome following the patient for one year with regression of the AR and amelioration of the patient’s clinical classification from NYHA IV to NYHA I